The Impact Of Business Environment And Government Support Towards Financial Performance: The Mediating Role Of Technological Innovation Among Private Listed Companies In China - Wang, Xiaoran (2024)
Firm financial performance is one of the key essential elements of financial management. Therefore, this research aims to investigate the effects of business environment (public administration, legal construction, foreign trade, and financial service) and government support (direct innovation subsidy and indirect fiscal expenditure) on the financial performance of private listed firms in China. This study also looks at how firm technological innovation plays a mediating role among business environment, government support and financial performance. This study covers 4,635 privately listed companies in China from 2013 to 2022, with a total of 30,351 observations. This study firstly adopts a fixed effects model for baseline regression. It is found that public administration, legal construction, foreign trade, financial service, direct innovation subsidy, and indirect fiscal expenditure are significantly and positively related to firm financial performance. Firm technological innovation positively mediates the relationship between business environment and government support on company financial performance. Secondly, in the robustness test, this study applied two-stage least squares, time segmentation, and alternative proxies to back up the findings of the baseline regression. The conclusions indicate that an optimised business environment and effective government support are key to improving firms’ financial performance.